The daily and shamanic dimensions of the relationship with the subarctic land for the semi-nomadic Athapaskan speaking Nabesna people on the Alaska-Yukon border, as taught by the women, in 1970 - Guédon, Marie-Françoise (Publications scientifiques du Muséum, 2022)
While most descriptions of nomadic societies begin with a male perspective to which is added later the role of women, the present text enters the Nabesna semi- nomadic way of life as defined by the women, with the men involved as primary actors in hunting but not necessarily as primary producers of the cultured environment. The Nabesna women conjugate their role as creators and keepers of the human environment, including dwellings, clothing and food preservation with their participation in hunting, food gathering, and other pursuits that take them away from the camp or the village in the forest, often by themselves. These contacts mean they have to develop their relationship with the non-human environment not only as predators but also as full-fledged participants in the shamanic web of communication and influence. Les dimensions quotidiennes et chamaniques des relations des Nabesnas, peuple athapaskan semi-nomade, avec le territoire subarctique, tel qu’enseignées par les femmes en 1970Alors que la plupart des descriptions de peuples chasseurs nomades débutent selon une perspective masculine à laquelle on ajoute le point de vue des femmes, les circonstances de mon travail sur le terrain m’ont amenée à entrer dans le contexte culturel des Nabesnas tel que perçu et vécu par les femmes. Dans cette société de chasseurs subarctiques, les femmes passent encore autant de temps que les hommes en dehors et loin du village ou du campement ? elles chassent, pêchent, et récoltent une grande partie des ressources alimentaires et autres, souvent en groupes, parfois seules. Mais autrefois, la diversité de leurs tâches et l’ampleur de leur participation aux déplacements des camps de chasse leurs donnaient un accès privilégié d’abord au territoire, ensuite au maintien et à la création de l’environnement humain, c’est-à-dire culturel, enfin aux puissances animales ou invisibles qui tissaient la trame chamanique de l’univers.Les Nabesnat’ani, ou Nabesnas, une dizaine de bandes ou groupes de familles, de deux cents à cinq cents ...